A study of consumer attitudes towards food court and fast food industry in Singapore. - Soh, Sok Hwee. (2008)
The project serves to find out the consumers’ perception of the importance of seven factors namely the quality of service, variety of food, price, promotion, location, quality of food and waiting time for seats, that affect their choice of visits to Fast Food restaurants or Food Courts. In addition, consumers’ levels of satisfaction with the respective restaurants are also assessed.